Association of Body Mass Index With Incidence and Progression of Knee Effusion on Magnetic Resonance Imaging and on Knee Examination. Issue 4 (24th March 2016) - Hung, Amy; Sayre, Eric C.; Guermazi, Ali; Esdaile, John M.; Kopec, Jacek A.; Thorne, Anona; Singer, Joel; Wong, Hubert; Nicolaou, Savvas; Cibere, Jolanda
Abstract : Objective: To determine the association of body mass index (BMI) with incidence and progression of knee effusion on magnetic resonance imaging (MRI) and physical examination (PE) in a longitudinal cohort with knee pain. Methods: A population‐based cohort was assessed at baseline and 3 years (n = 163). BMI was categorized as normal (<25), overweight (25–29.9), and obese (≥30). Knee effusion was graded as 0–3 (absent/mild/moderate/severe) on MRI and 0–1 (absent/present) on PE. Progression of MRI effusion (MRIeff ) was an increase of ≥1 grade in those with grade 1 or 2 at baseline. Incident MRIeff and PE effusion (PEeff ) were any effusion at followup (>0) in those with grade 0 at baseline. A second type of incident MRIeff was effusion grade ≥2 at followup in those with grade <2 at baseline. Exponential regression analysis was used, adjusted for age, sex, and radiographic severity. Results: Incident MRIeff ≥1, incident MRIeff ≥2, incident PEeff, and progression of MRIeff were seen in 14 of 73 (19%), 18 of 140 (13%), 26 of 127 (20%), and 18 of 86 (21%), respectively. There was a borderline statistical association of obesity with progression of MRIeff (hazard ratio [HR] 3.3 [95% confidence interval (95% CI) 1.0–11.2]) and with incident MRIeff ≥2 (HR 3.4 [95% CI 1.0–11.5]). BMI was not associated with incident MRIeff ≥1 (HR overweight 1.1 [95% CI 0.3–3.6], obese 1.0 [95% CI 0.2–5.0]). Overweight was associated with incident PEeff (HR 4.5 [95% CI 1.4–14.2]), while obesity was not statistically significant (HR 3.1 [95% CI 0.9–11.1]). Conclusion: Obesity was a risk factor for incident and progressive knee effusion in this population‐based cohort. These findings highlight an important link between obesity and inflammation in knee osteoarthritis.